A Review of Efficacy and Safety of Checkpoint Inhibitor for the Treatment of Acute Myeloid Leukemia - Liao, Dan; Wang, Mengyao; Liao, Yi; Li, Jun; Niu, Ting (Frontiers in Pharmacology, 2019)
Acute myeloid leukemia(AML)is a form of cancer originated from malignant clonal stem cells in bone marrow marked by heterogenous clinical outcome due to the complexity of its molecular and cytogenetic architecture. The longstanding standard regimen for AML treatment is induction therapy with 3 days of an anthracycline and 7 days of standard-dose cytarabine followed by consolidation chemotherapy or bone marrow transplantation. Despite the optimized induction regimen and progress in recognizing molecular heterogeneity of AML which helps to stratify patients, the outcome for older patients who represent the majority of the population remains dismal and the relapse of leukemia, particularly after transplantation, is challenging to manage. Novel therapeutic strategies are in desperate need. Immune checkpoint inhibitors(ICIs)  as positive modulators of immune response have achieved impressive efficacy in melanoma and numerous solid tumor malignancies. For AML, the success of allogenic stem cell transplantation where graft-versus-leukemia effect significantly contributes to anti-neoplastic response makes it potential beneficiary for checkpoint inhibition treatment. Programmed-death 1(PD-1)and cytotoxic T-lymphocyte-associated protein 4(CTLA-4) are the two most actively investigated checkpoint receptors. Early data from ongoing clinical trials demonstrates therapeutic promise of checkpoint inhibitors for treating AML patients with improved overall response rate compared with traditional therapy as well as reversible side effects. Single anti-PD-1 monoclonal antibody(CT-011) infusion shows rather modest clinical efficacy. While combinations of  PD-1 inhibitor nivolumab with hypomethylating agents(HMA) azacitidine represent encouraging outcome for relapsed/refractory(R/R) AML patients with higher overall response rate(ORR) compared with single agent HMA therapy. More rationally designed combinations are under investigation for better clinical response. CTLA-4 inhibitor ipilimumab exhibits specific potency in treating relapsed AML patients in later post-transplantation stage. Immune-related adverse events(irAEs) are of great concern to doctors. irAEs found in these trials can mostly be appropriately managed with steroids but are occasionally fatal. A good awareness of the inflammatory toxicities and early intervention with appropriate treatment are critical for outcome improvement. This article reviews data from several phase I、II clinical trials that evaluating PD-1 and CTLA-4 inhibitors on AML patients and discusses especially efficacy and adverse events as well as prospects of these drugs in treating acute myeloid leukemia.